Association between health literacy and adopting preventive behaviors of breast cancer in Iran - Rahman Panahi; Peyman Namdar; Fatemeh Samiei Siboni; Somayeh Fallah; Mohammad Anbari; Leila Dehghankar; Leili Yekefallah; Mahya Shafaei (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Health literacy plays an important role in adopting preventive behaviors. Considering the relatively high prevalence of breast cancer in women, this study aimed to assess the association between health literacy and adopting the preventive behavior of breast cancer in Iran . METHODS: This was a descriptive, cross-sectional study, in which 375 female students at Imam Khomeini International University in Qazvin in the academic year of 2018-2019 were selected through a stratified random sampling method. Demographic and background questionnaire, the standard questionnaire of Health Literacy for Iranian Adults in addition to another questionnaire for measuring breast cancer preventive behaviors, were used for collecting data. Data were analyzed using SPSS 22 using descriptive statistics and logistic regression. RESULTS: The mean of the breast cancer preventive behaviors and health literacy were 8.92 ± 1.82 out of 16 and 70.80 ± 12.49 out of 100. Regression results showed that there was a statistically significant association between the adoption of breast cancer preventive behaviors and physical activity (P < 0.001) and health literacy (P < 0.018). Accordingly, the chance for adopting the preventive behaviors in good level among students with rare and without physical activity was 0.105 and 0.100 times, respectively, more than students who had been doing physical activity on a daily basis. Moreover, the same chance among students with adequate and very adequate health literacy was 1.802 and 2.169 times more than students with inadequate health literacy. CONCLUSION: The results indicated that students with lower levels of health literacy and less physical activity had shown less tendency to adopt preventive behaviors of breast cancer. Therefore, special attention should be paid to health literacy (HL), particularly physical activity, application of health information, and assessment in students when designing educational programs to prevent breast cancer.